Does Debts have any Impact on Governance Bundle and Agency Costs? Over-Governance Hypothesis - Khatib, Saleh F.A.; Fariha Abdullah, Dewi; Shariff Kabara, Ali; Hazaea, Saddam A.; Selvi Rajoo, Tamil (Technium Social Sciences Journal, 2020)
The purpose of this article is to extend the bundles of corporate governance theory and propose the role of corporate debt in determining the governance structure of a company. This research intended to answer some questions have been put forward by scholars to explain the inter-relationship between debt, corporate governance, and agency costs: (i) what exactly is the disciplinary role of debts? (ii) how is governance structure influenced by the debt level? and (iii) are extremely high debt ratios required? Previous works have looked at interrelations between debt, corporate governance, and agency costs in isolation result in inclusive findings. However, we argue that debt level is a key determinant of the effective governance structure that maintains agency costs at the optimal level. Based on the governance bundle theory, we contribute to the literature by introducing a new model (over-governance model) that suggests financial leverage as a critical contingency linking governance bundle and agency costs. Also, it provides a clear picture on the different type of agency costs. Our paper provides a theoretical framework to guide further studies and provide important implications for the board, corporate management, and regulators.